Upgrading and Global Value Chain 4.0: The Case of Palm Oil Sector in Indonesia - B. Endo Gauh Perdana (Global South Review, 2019)
The Industrial Revolution 4.0 promotes digitalization and innovation across many sectors of industries allowing them to thrive by increasing productivity, profitability, product quality and performance. However, the utilization of digital technology especially in agricultural sector, requires effective governance in which must adhere to sustainability practices for upgrading strategies. As one of the main export commodities in Indonesia, the palm oil industry is in alert to face challenges brought by the Industrial Revolution 4.0. This research draws from the latest work of Gerrefi and Lee on Global Value Chain. In the framework of horizontal industrial cluster and vertical global value chain governance, the theory examines how governance and upgrading trajectories produces economic upgrading which correlates to social and environmental upgrading. This research, then scrutinizes the question posed by the role of technology which supports as well as accelerates the upgrading strategies. The GVC analysis of Indonesian palm oil industry will be used as a case study to understand the complexity of how actors operate in every cluster of governance. Economic upgrading is not always associated with social and environmental upgrading. Therefore, a strong linkage between actors suggests that the Industrial Revolution 4.0 is relevant and essential to enhance synergy to cater for economic, social and environmental dimensions in order to harness the potential of sustainable development.